The Solution of the Main Fan Station for Underground Mines Being Decommissioned in Terms of Reducing Energy Consumption by Ventilation - Nikodem Szlązak; Marek Korzec (Energies, 2022)
Ventilation plays a key role in underground mining. It is essential due to the natural hazards and technological processes that come with the nature of mining. However, it is highly energy consuming and generates significant operating expenditures. Fan station parameters are selected based on the needs of a particular mine but mainly consider the requirements for the period of developed mining activities. When the period of mine decommissioning begins, the parameters of the main fan station often exceed its needs. In Poland, many mines have been closed in recent years. However, sometimes, due to the necessity of pumping underground water, it cannot be done thoroughly. In such a situation, it usually turns out that the parameters of the existing fan station significantly exceed the mine’s needs. The main fan stations are devoid of control systems, and even if they have them, they do not allow for a significant reduction of their volume flow rate. Modernising of the station to meet new requirements of the mine is expensive and time consuming. Solving the presented problem is possible by developing a fan station to replace main fans that are too big. The idea is easy to implement and consists of connecting it to an existing upcast shaft or downcast shaft, which will then be changed to upcast. The solution presented in the article has been implemented in two Polish coal mines and is in progress in a third mine. The examples presented in the article clearly show the energy benefits of replacing main fans that are too large.